The Reason for Dispute among Foundational Jurists in the Science of "Jurisprudence" between Certainty and Conjecture - Mohammed Ali M. Alasmari; Musallam Bakheet M Aljohani (Kurdish Studies, 2024)
This study addresses the reason for the dispute concerning the certainty and conjecture of jurisprudential knowledge. I clarified the dispute's context, where scholars are divided into two groups: those who consider jurisprudential knowledge as definitive, and others who view it as conjectural. I then illustrated the dispute's basis, which stems from three reasons: firstly, the definition of jurisprudence in terms of terminology or as a designation; secondly, the disagreement over interpreting the term "knowledge" and its intended meaning; thirdly, the issue of validating or invalidating the efforts of a jurist (Ijtihad). The study concludes with several recommendations: attention to studying the reasons for disputes in fundamental issues, elucidating their interconnections, a deeper examination of the definitions of jurisprudence and knowledge in Islamic jurisprudence, clarifying concepts and terminologies as per foundational, linguistic, and jurisprudential perspectives, conducting further research on the role of Ijtihad and its impact on Islamic rulings and scholars' perceptions in this context, focusing on understanding disputes related to validating or invalidating juristic efforts, and analyzing more sharia and foundational texts related to conjecture and certainty in jurisprudence. God grants success.